rDNA-RFLP identification of Candida species in immunocompromised and seriously diseased patients - Pinto, Patrícia M.; Resende, Maria A.; Koga-Ito, Cristiane Y. [UNESP]; Ferreira, José A.G.; Tendler, Miriam (Canadian Science Publishing, 2004)
PCR was used to amplify a targeted region of the ribosomal DNA of 76 Candida spp. isolates from immunocompromised and seriously diseased patients. Thirty-seven strains isolated from different anatomical sites of 11 patients infected with HIV (Vitória, ES, Brazil), 26 isolates from patients under treatment at Odilon Behrens Hospital and 13 isolates from skin and urine samples from São Marcos Clinical Analysis Laboratory (Belo Horizonte, Brazil) were scored. Fragments of rDNA were amplified using primer pairs ITS1-ITS4, for the amplification of ITS1 and ITS2 regions, including the gene for the 5.8s subunit. Amplification resulted in fragments ranging in size from 350 to 950 bp. Amplicons were digested with eight restriction enzymes. A pattern of species-specificity among the different medically important Candida species could be identified following restriction digestion of the PCR products. Candida albicans was the species most frequently observed, except for the group of newborns under treatment at the Odilon Behrens Hospital and for the isolates from the clinical analysis laboratory. C. parapsilosis was the species most frequently observed in these two groups.
Keywords: Candida spp.; Candidosis; Polymerase chain reaction; Restriction fragment length polymorphism; Biodiversity; Body fluids; DNA; Enzymes; Hospitals; Immunology; Patient treatment; Viruses; Candida species; Clinical analysis laboratory; Fragments; Urine samples; Microbiology; restriction endonuclease; ribosome DNA; human immunodeficiency virus; identification method; polymerase chain reaction; amplicon; Candida; Candida albicans; candidiasis; controlled study; disease severity; fungus identification; gene amplification; human; immune deficiency; nonhuman; opportunistic infection; priority journal; restriction fragment length polymorphism; skin; species difference; urine; Candidiasis; Cluster Analysis; DNA Fingerprinting; DNA Restriction Enzymes; DNA, Fungal; DNA, Ribosomal; DNA, Ribosomal Spacer; Epidemiology, Molecular; Genes, rRNA; Humans; Immunocompromised Host; Mycological Typing Techniques; Phylogeny; Polymerase Chain Reaction; Polymorphism, Restriction Fragment Length; RNA, Ribosomal, 5.8S; Candida parapsilosis; Fungi; Human immunodeficiency virus